Economic thought in the Soviet Union: Concepts and aspects. A comparative outline - Guelfat, Isaac; International Centre of Research and Information on Collective Economy (Liège, C.I.R.I.E.C.; The Hague, Martinus Nijhoff, 1969)
In this text the author is mainly concerned with a number of concepts and notions current in literature on the subject which were and are still accepted in general economic science. The author concentrated on explaining the substance of the categories and notions of Soviet economic theory. The book is divided into two parts. Part I. Concepts and Aspects. Part II. Recent Developments.
Bibliography: p. [151]-157.
rpm 30/10/2017
Loans
Keywords: Economics; Economic conditions; Soviet Union